PERSONNEL TRAINING ON A «TURNKEY» BASIS - Sergey A. Mikhailichenko (Высшее образование в России)
The article focuses on the problem of arranging practiceGoriented education at technical university. The basic steps in this direction are the establishment of the University of Applied Sciences of BSTU, implementation of the dual education system, university cooperation with enterprises for future employment of graduates, creating a Scillbook web-resource based on BSTU portal, aimed at rendering assistance in graduates’ job placement.